Working memory moderates the predictive influence of distress intolerance on health-related goal attainment. Issue 2 (4th March 2021) - Fitzgerald, Hayley E.; Gorlin, Eugenia I.; Otto, Michael W.
ABSTRACT: High distress intolerance (DI: often assessed as anxiety sensitivity) and low working memory capacity (WMC) have each been identified as risk factors for negative health behaviors. To our knowledge, these risk factors have only been studied independently. The current study investigated both the independent and interactive effects of DI and WMC in predicting health-related goal attainment in 118 undergraduates who self-selected a health-related goal. Participants received one of three interventions: values clarification, action planning, or a combination of the two. Across these interventions, we found that DI was at the point of significance (and reflected a small effect size) for predicting goal attainment, whereas WMC was not. Further, we found that when entered into the stepwise regression model together, the interaction of WMC and DI significantly predicted goal success one week later. Specifically, for individuals scoring one standard deviation below the mean in WMC, having worse DI significantly predicted worse goal attainment one week later. We believe this study represents the first published finding of the moderation of the predictive influence of DI by WMC, and underscores the importance of evaluating how risk factors that are typically examined independently operate together.